ANÁLISE DA CITOTOXICIDADE DOS ARROIOS ESPINHO E MOINHO DO MUNICÍPIO DE IJUÍ, RS - MARIZA DOS SANTOS AGERTT , FLÁVIA; MARIA FACHINETTO , JULIANA; MATZ GUTKNECHT , MARIANA; THÉRESE AYGADOUX MARTINS , CAROLINE (Salão do Conhecimento, 2021)
Citotoxicidade